ORGANIZATIONAL SILENCE: SUATU PENGHAMBAT DALAM MEWUJUDKAN KREATIFITAS ORGANISASIONAL - Berta Bekti Retnawati (KINERJA, 2003)
There are powerful forces in many organzations that cause widespread withholding of information about potential problems or issues by employess, this collective-level phenomenon as ‘organizational silence’. One significant effect of organizational silence relates to lack of organizational creativity.There are five major organizational factors that enhance creativity in a work environment: organizational climate, leadership style, organizational culture, resources and skills, the structure and system of an organization.Keywords: organizational silence, organizational creativity